Experimental study of ultra-low IFT foam flooding for low permeability reservoirs - Lang, Liyuan; Zhao, Shuang; Liu, Lu (Frontiers in Energy Research, 2024)
Foam flooding is an effective oil displacement technique to improve fluid sweep efficiency and increase oil recovery. The objective of this paper is to investigate the applicability of ultra-low IFT foam flooding for low permeability oil recovery under the conditions of WX reservoir block in Tuha oilfield (84℃, 86072mg/L).A modified amphoteric hydroxy sulfobetaine surfactant (Cn-HSB) was formulated as a foaming agent based on the principle of compatibility with crude oil that could achieve the ultra-low interfacial tension (IFT) and strong foamability simultaneously. This is shown to reduce the oil/water dynamic IFT (DIFT) to an ultra-low value of the order of 10 -5 mN/m (0.10wt%), as well as produce a foam volume and half-life of 448mL and 2567s, respectively. In addition, results of IFT and foam quality tests indicate that the modified Cn-HSB has good thermal stability and excellent salinityresistance. Moreover, the ultra-low IFT foam flooding has an ideal injectivity and oil displacement efficiency in low permeability porous media that can mobilize the trapped oil in k=1.50×10 -3 μm 2 with a threshold pressure gradient of 0.115MPa/m. This improves oil displacement efficiency about 15%OOIP.Fundamental knowledge gained from this research gives insight into the application of ultra-low IFT foam flooding in low-permeability reservoirs under a combination of specific reservoir conditions.